What Makes Students Adjust to University? The Predictors of College Adjustment: Systematic Literature Review - Anandhika Agus Saputra; Rudi Cahyo (STKIP Yapis Dompu, 2023)
For many students, starting college marks a significant transition. Students must face many transitions as they enter college, including changes in their life, academic environment, social environment, and adjusting to their independence and responsibilities. Although many students successfully make the transition to college, The importance of transition and adjustment for students in their first year is fascinating to investigate, and this paper investigates college adjustment predictors in assisting students and first-year student in their transition to university. A systematic literature review will turn up several articles on transitions and adjustment of first-year students. The goal of this review is to determine the predictors of college adjustment. According to the findings of a literature review, there are four domain factors that are predictors of college adjustment: personality trait factors, external factors, coping style factors, and demographic factors. The limitation of this review may be added during the selection of the articles, the setting of the articles is not chosen specifically implying the countries are mixed between continents randomly, also the articles chosen are only limited from English language only, implying that the articles written in developing countries are not included and reviewed.